Case report: Long-term follow-up of patients who received a FimCH vaccine for prevention of recurrent urinary tract infections caused by antibiotic resistant Enterobacteriaceae: a case report series - Perer, Elise; Stacey, Helen; Eichorn, Terri; Hughey, Heidi; Lawrence, Julie; Cunningham, Eric; Johnson, Mark O’Neil; Bacon, Kevin; Kau, Andrew; Hultgren, Scott J.; Hooton, Thomas M.; Harris, Jennifer L. (Frontiers in Immunology, 2024)
Urinary tract infections (UTI) caused by carbapenem-resistant Enterobacteriaceae (CRE) are considered one of the most urgent health threats to humans according to the Centers for Disease Control (CDC), and the World Health Organization (WHO). A FimCH Vaccine expanded access study is being conducted in patients with a history of antibiotic resistant UTIs who are considered to be at risk for development of CRE UTI. This case series describes the clinical, safety and immunogenicity findings for four participants who received a FimCH four-vaccine series. Participants were followed for 12 months after administration of the fourth vaccine for safety, general health status and UTI occurrence. The study was later amended to allow additional follow-up of up to five years post vaccine administration to assess long-term health status, UTI occurrences and to obtain blood samples for anti-FimH antibody testing. In our population of 4 study participants, the number of symptomatic UTI occurrences caused by gram-negative bacteria in the 12-month period following peak anti-FimH antibody response were approximately 75% lower than the 12-month period preceding study enrollment. These results are consistent with the 30-patient cohort of a Phase 1 study with the same FimCH Vaccine. UTI occurrences increased during the long-term follow-up period for all 4 participants but did not reach the rate observed pre-vaccination. No new safety concerns related to the FimCH Vaccine were identified during long-term follow-up. This case series has clinical importance and public health relevance since it examines and reports on UTI frequency and recurrence following vaccination with the FimCH Vaccine in a high-risk population of patients with recurrent UTI. Additionally, participants described improved well-being following vaccination which was maintained in the long-term follow-up period.